Mueller polarimetric imaging for fast macroscopic mapping of microscopic collagen matrix remodeling by smooth muscle cells - Olga Chashchina (Nature Portfolio, 2021)
Abstract Smooth muscle cells (SMCs) are critical players in cardiovascular disease development and undergo complex phenotype switching during disease progression. However, SMC phenotype is difficult to assess and track in co-culture studies. To determine the contractility of SMCs embedded within collagen hydrogels, we performed polarized light imaging and subsequent analysis based on Mueller matrices. Measurements were made both in the absence and presence of endothelial cells (ECs) in order to establish the impact of EC-SMC communication on SMC contractility. The results demonstrated that Mueller polarimetric imaging is indeed an appropriate tool for assessing SMC activity which significantly modifies the hydrogel retardance in the presence of ECs. These findings are consistent with the idea that EC-SMC communication promotes a more contractile SMC phenotype. More broadly, our findings suggest that Mueller polarimetry can be a useful tool for studies of spatial heterogeneities in hydrogel remodeling by SMCs.